Endothelial Dysfunction in Chronic Kidney Disease, from Biology to Clinical Outcomes: A 2020 Update - Roumeliotis, Stefanos (J Clin Med, 2020)
The vascular endothelium is a dynamic, functionally complex organ, modulating multiple biological processes, including vascular tone and permeability, inflammatory responses, thrombosis, and angiogenesis. Endothelial dysfunction is a threat to the integrity of the vascular system, and it is pivotal in the pathogenesis of atherosclerosis and cardiovascular disease. Reduced nitric oxide (NO) bioavailability is a hallmark of chronic kidney disease (CKD), with this disturbance being almost universal in patients who reach the most advanced phase of CKD, end-stage kidney disease (ESKD). Low NO bioavailability in CKD depends on several mechanisms affecting the expression and the activity of endothelial NO synthase (eNOS). Accumulation of endogenous inhibitors of eNOS, inflammation and oxidative stress, advanced glycosylation products (AGEs), bone mineral balance disorders encompassing hyperphosphatemia, high levels of the phosphaturic hormone fibroblast growth factor 23 (FGF23), and low levels of the active form of vitamin D (1,25 vitamin D) and the anti-ageing vasculoprotective factor Klotho all impinge upon NO bioavailability and are critical to endothelial dysfunction in CKD. Wide-ranging multivariate interventions are needed to counter endothelial dysfunction in CKD, an alteration triggering arterial disease and cardiovascular complications in this high-risk population.